Pemanfaatan Air Gambut Untuk Meningkatkan Kualitas Produksi Biocoal dari Limbah Tandan Kosong Kelapa Sawit Dengan Variasi Waktu dan Temperatur Proses Torefaksi - Martin, Awaludin (Rekayasa, 2021)
Efforts to increase the use of new and renewable energy continue to be carried out where the one of the programs is to seek the use of mixed fuels (co firing) in fossil fuel power plants such as steam power plant. The main fuel in steam power plant mostly uses coal and the mixed fuel can be used as biomass fuel. Palm oil empty fruit bunches are one of the potentially large biomass that can be used as mixed fuel because of its abundant availability, especially in Riau Province. However, palm oil empty fruit bunches have a low heating value of combustion, so the treatment needs to be carried out in order to palm oil empty fruit bunches as biomass fuel have a high heating value. This study aims to increase the heating value of palm oil empty fruit bunches by torrefaction process so that palm oil empty fruit bunches have a high heating value and equivalent to the heating value of coal. The torrefaction process is carried out with variations in time and temperature of torrefaction, namely 30 - 60 minutes and 200oC - 300oC. The research carried out results in the largest heating value of 7470.59 kcal/kg at a time process of 60 minutes and a torrefaction temperature of 300oC.